The nexus between firm size, growth and profitability: new panel data evidence from Asia–Pacific markets. Issue 1 (5th August 2021) - Yadav, Inder Sekhar; Pahi, Debasis; Gangakhedkar, Rajesh
Abstract : Purpose: The purpose of this paper is to examine the correlation between firm size, growth and profitability along with other firm-specific variables (like leverage, competition and asset tangibility), macroeconomic variable (like GDP growth-business cycle) and stock market development variable (like MCR). Design/methodology/approach: Using the COMPUSTAT Global database this work uses panel dynamic fixed effects model for nearly 12, 001 unique non-financial listed and active firms from 1995 to 2016 for 12 industrial and emerging Asia–Pacific economies. This interrelationship was also examined for small, medium and large size companies classified based on three alternate measures such as total assets, net sales and MCR of firms. Findings: The persistence of profits coefficient was found to be positive and modest. There is evidence of a negative size-profitability and positive growth-profitability relationship suggesting that initially profitability increases with the growth of the firm but eventually, overtime, gains in profit rates reduce, as size increases indicting that large size breeds inefficiency. The relationship between firm's leverage ratio and its asset tangibility is found to be negative with profitability. The business cycle and stock market development variables suggest a positive relationship with the profitability of firms. However, the significance of estimated coefficients was mixed and varied among different selected Asia–Pacific economies. Practical implications: The study has economic implications on issues such as industrial concentration, risk and optimum size of firms for practicing managers of modern enterprise in emerging markets. Originality/value: The analysis of the relationship between the firm size, growth and profitability is uniquely determined under a dynamic panel fixed effects framework using firm-specific variables along with macroeconomic and financial development determinants of profitability. This relationship is estimated for a large and new data set of 12 industrial and emerging Asia–Pacific economies. Abstract : 研究目的: 本研究擬探討公司的規模、成長和盈利能力之間的關係， 同時亦涵蓋公司特有的其它變量 （如愩杆作用， 競爭和資產的有形性）， 宏觀經濟變量 （如國內生產總值增長與景氣之循環）， 以及股市發展變量 (如MCR) 。 研究的設計/方法/理念: 本研究以COMPUSTAT 全球資料庫、使用動態面板固定效應模型，涵蓋幾近12001間獨特的、非金融上市及活躍的公司、覆蓋期由1995年至2016年，涉及12個工業及新興的亞太經濟體。這相互關係分析研究亦於大、中及小型企業內進行，而這些企業就規模方面的分類是基於三個交替的測量而釐定的，如總資產、銷售淨額、以及企業的MCR。 研究結果: 研究發現、利潤係數的持續性是正且適中不強的。有證據顯示、規模的大小與盈利能力是負相關的，而增長與盈利能力則為正相關；這暗示盈利能力初時會因企業的成長而增強，但隨著時間的推移最终當規模增大、利潤率的增長會下降，這提示我們：大的規模會導致效率低下。企業的杠桿比率與其資產有形性的關聯被發現與盈利能力成負相關。經濟週期及股市發展變量暗示與企業的盈利能力之關聯為正相關。唯估計係數的意義會因被挑選之各個不同亞太經濟體而有異和不統一的。 實際的意義: 本研究對在新興市場的現代企業內工作的業務經理有其實際作用，因研究為他們在業務問題如產業集中度、危機、公司的最佳規模等問題上提供了經濟方面的啟示。 研究的原創性/價值: 本研究分析公司規模、成長與其盈利能力的關係時，獨特之處是採用了動態面板固定效應模型，並於應用盈利能力的宏觀經濟和金融發展的決定因素的同時，也使用了企業特有的變量。而這關係的分析研究涵蓋12個工業及新興的亞太經濟體的龐大且新的數據集。